2006
DOI: 10.1037/0278-7393.32.6.1322
|View full text |Cite
|
Sign up to set email alerts
|

Readers' experiences of characters' goals and actions.

Abstract: In this article, the authors examined readers' sensitivity to the match between characters' goals and characters' actions. In Experiment 1, readers integrated actions consistent with characters' goals more easily when there was a match between the extremeness of the actions and the urgency of the goals. In Experiments 2 and 3, characters' actions were consistent with either explicit or implicit goals. Participants showed different sensitivity to the mismatch between actions and urgent goals when they simply re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 25 publications
0
30
0
1
Order By: Relevance
“…However, this generalization holds for moment-by-moment integration processes, but not necessarily for reflective processes. Readers understand characters' actions in reference to a recent, local goal during moment-by-moment reading, and in reference to a more urgent, distal goal when formulating judgments (Egidi & Gerrig, 2006). Recent neuroimaging studies (e.g., Hasson, Nusbaum, & Small, 2006) also support the dissociation between natural comprehension and reflective processing of language, since these studies have shown that the two rely-at least partially-on different functional networks.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…However, this generalization holds for moment-by-moment integration processes, but not necessarily for reflective processes. Readers understand characters' actions in reference to a recent, local goal during moment-by-moment reading, and in reference to a more urgent, distal goal when formulating judgments (Egidi & Gerrig, 2006). Recent neuroimaging studies (e.g., Hasson, Nusbaum, & Small, 2006) also support the dissociation between natural comprehension and reflective processing of language, since these studies have shown that the two rely-at least partially-on different functional networks.…”
mentioning
confidence: 96%
“…Reading often prompts integration with a large amount of information, especially when access to the distal portion of the text is necessary (Albrecht & Myers, 1995Gerrig & O'Brien, 2005), but such access does not always take place (Egidi & Gerrig, 2006;McKoon & Ratcliff, 1992;O'Brien & Myers, 1999). In contrast, the judgment task that we used involves the formulation of a novel judgment (that presupposes successful integration) and by definition requires evaluating the ending of a story with respect to a large amount of information-that is, the entire story.…”
mentioning
confidence: 99%
“…However, the particular body of psychological research drawn upon here is a series of journal publications which all, to some degree, investigate how readers experience and react to different stories or to different versions of the same story (Egidi and Gerrig 2006;Gerrig and Rapp 2004;Rapp and Gerrig 2006). A short overview of these studies follows, and thereafter the remainder of this section narrows in focus to consider one particular narrative mechanism which features in this collection of work.…”
Section: Introductionmentioning
confidence: 99%
“…In their study of the way reading times are influenced by characters' goals in a story, Egidi and Gerrig (2006: passim) argue that readers generally tend to identify with characters' goals the more 'urgently' those goals are narrated. More specifically, they point out that readers are 'responsive to the match between the urgency of characters' goals and the means characters take to achieve those goals' (Egidi andGerrig 2006: 1323). Elsewhere, they talk of 'urgent motivation' (1326), of 'mild and urgent goals ' (1325) and of goals of 'moderate or urgent importance ' (1326).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation